Spray drift deposition comparison of fluorimetry and analytical confirmation techniques. Issue 9 (17th May 2021) - Szarka, Arpad Z; Kruger, Greg R; Golus, Jeff; Rodgers, Carol; Perkins, Daniel; Brain, Richard A
Abstract: Tracer dyes are often used as surrogates to characterize pesticide spray drift and it is assumed that they accurately reflect analytical measurement of active ingredients; however, the validity of this assumption remains inconclusive. Consequently, the influence of measurement technique on the magnitude of deposition of spray drift was investigated using spray drift samples evaluated by traditional analytical techniques (HPLC–MS/MS) and fluorimetry (1, 3, 6, 8‐pyrene‐tetra sulfonic acid tetrasodium salt dye tracer). The experiment was conducted in a low‐speed wind tunnel under controlled meteorological conditions. The herbicide mesotrione was sprayed through three spray air induction nozzles (anvil deflector flat fan TTI11004; flat fan AI11004; flat fan AIXR11003). Spray drift deposition samples were collected using stainless steel discs pairs placed side by side in the center of the wind tunnel at distances of 5, 10, 20, 30, and 40 ft (1.5, 3.1, 6.1, 9.1, and 12.2 m) from the spray nozzle. The analytical technique determined pesticide concentration on one disc per pair, and the other was evaluated by fluorimetry. The experimental results, analyzed using the linear split‐split plot model, revealed that median deposition concentrations were 15% higher using the tracer dye fluorescence method relative to the analytical method, potentially due in part to procedural recovery inefficiencies of the analytical method (the mean overall procedural recovery result and RSD was 87% ± 6.4% (n = 12). This relationship was consistent and held true for the three nozzle types at all distances within the wind tunnel. © 2021 Society of Chemical Industry. Abstract : Direct comparison between dye tracer and analytical verification methods demonstrated that fluorescence can provide consistent and conservative estimates of spray drift deposition for the purposes of pesticide risk assessment.